Pooling Rectal, Pharyngeal, and Urine Samples to Detect Neisseria gonorrhoeae, Chlamydia trachomatis, and Mycoplasma genitalium Using Multiplex Polymerase Chain Reaction Is as Effective as Single-Site Testing for Men Who Have Sex With Men. (31st October 2022) - Prazuck, Thierry; Lanotte, Philippe; Le Moal, Gwénaël; Hocqueloux, Laurent; Sunder, Simon; Catroux, Mélanie; Garcia, Magali; Perfezou, Pascale; Gras, Guillaume; Plouzeau, Chloé; Lévêque, Nicolas; Beby-Defaux, Agnès
Abstract: Background: Screening for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) at pharyngeal, urogenital, and anorectal sites is recommended for men who have sex with men (MSM). Pooling samples is a promising technique, but no data are available when pooled screening also includes Mycoplasma genitalium (MG). The main objective of this study was to examine the sensitivity of pooled samples for detecting CT, NG, and MG in MSM using nucleic acid amplification versus single-site testing. Methods: In this multicenter study, MSM with a positive result for CT, NG, or MG were recalled to the clinic for treatment and were asked to participate in this study. Separate samples were sent to a central virological department that proceeded to form the pooled samples. Testing was performed using the multiplex real-time polymerase chain reaction Allplex STI Essential Assay (Seegene, Seoul, Korea), which can simultaneously detect 7 pathogens. Results: A total of 130 MSM with at least 1 positive test for CT, NG, or MG were included. A total of 25.4% had a coinfection. The sensitivities of pooled-sample testing were 94.8% for CT, 97.0% for NG, and 92.3% for MG. Pooling failed to detect 8 infections, but pooled-sample analysis missed detecting only samples with a low bacterial load (cycle threshold >35). Conclusions: Pooling samples from MSM to detect CT, NG, and MG is as sensitive as individual-site testing for these 3 pathogens using the Allplex assay. Missed infections with a very low bacterial load could have a low impact on further transmission. Clinical Trials Registration. NCT03568695. Abstract : Among 130 MSM with Chlamydia trachomatis, Neisseria gonorrhoeae, and/or Mycoplasma genitalium infection, pooling samples was as effective as individual site testing, with sensitivities of 94.8%, 97.0%, and 92.3%, respectively. Missed detection occurred only for samples with a low bacterial load.